The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1584/jpestics.g09-67
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Japanese Fusarium graminearum species complex isolates to metconazole

Abstract: The sensitivity of the Fusarium graminearum species complex, the causal fungus of Fusarium head blight, to metconazole was measured. The minimum inhibitory concentrations (MIC) of 101 isolates ranged from 0.20 to 6.25 mg/l with a single peak at 1.56 mg/l. The effective concentration for 50% growth inhibition (EC 50 ) was Ͻ0.1 mg/l in about 80% of isolates, and no isolate was significantly less sensitive to metconazole among this group. Among the F. graminearum species complex, F. asiaticum and F. graminearum s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…In China, Yin et al, (2009) assessed sensitivity of 40 F. graminearum isolates to tebuconazole and found a EC 50 mean of 0.248 mg/L (0.021-1.152 mg/L), which is much higher than those found in our study to both fungicides tested. However, in Japan, Tateishi et al (2010) studied 101 isolates representing F. graminearum and F. asiaticum populations and found that 80% of isolates showed EC 50 towards metconazole of less than 0.1mg/L, a level of sensitivity more similar to that found in the present study.…”
supporting
confidence: 82%
See 1 more Smart Citation
“…In China, Yin et al, (2009) assessed sensitivity of 40 F. graminearum isolates to tebuconazole and found a EC 50 mean of 0.248 mg/L (0.021-1.152 mg/L), which is much higher than those found in our study to both fungicides tested. However, in Japan, Tateishi et al (2010) studied 101 isolates representing F. graminearum and F. asiaticum populations and found that 80% of isolates showed EC 50 towards metconazole of less than 0.1mg/L, a level of sensitivity more similar to that found in the present study.…”
supporting
confidence: 82%
“…Fungicide sensitivity was quantified by measuring the radial growth of the cultures on PDA (potato dextrose agar) media (Becher et al, 2010;Tateishi et al, 2010) amended with increasing concentrations of tebuconazole (Tebuconazole Nortox 200 EC, Nortox S.A.) or metconazole (Caramba 90, BASF S.A.) (0.0; 0.01; 0.05; 0.1; 1 and 10 mg/L). The fungicides were added to PDA media in three replicates each.…”
mentioning
confidence: 99%
“…In general, fungicides containing triazole as the active ingredient (metconazole, prothioconazole and tebuconazole) are considered the most effective chemical compounds against Fg (8, 12,15,17,20,21,27).…”
Section: In Vitro Sensitivity Reduction Of Fusarium Graminearum To Dmmentioning
confidence: 99%
“…In previous studies, similar results were detected in the Jiangsu F. graminearum population to metconazole with EC 50 values ranging from 0.0209 to 0.0838 μg/ml and an average of 0.0481 ± 0.0134 μg/ml (Duan et al, ). The mean EC 50 value of the Brazilian F. graminearum population from wheat fields was 0.037 μg/ml (Spolti et al, ), and the EC 50 value of 80% of 101 F. graminearum isolates recovered from wheat fields in Japan was lower than 0.1 μg/ml (Tateishi et al, ). These findings confirm that the DMI fungicide metconazole could effectively inhibit the mycelial growth of F. graminearum .…”
Section: Discussionmentioning
confidence: 99%